Anti-Immigrant Ordinances and Discrimination in New and Established Destinations. (November 2014) - Ebert, Kim; Ovink, Sarah M.
Immigrants and their children come to the U.S. in search of upward mobility, but in many contexts they experience discrimination and restrictive political climates. Contexts vary widely, however, given the growing number of new immigrant destinations. Past studies tend to focus on what immigrants and their children are (or are not) doing to adapt to local contexts, a focus that strengthens the perception that immigrants are a "problem" group. In this article, we move the debate away from more familiar economic analyses to assess how destination type and exclusionary ordinances, defined as laws that restrict the rights of and services accorded to immigrant groups, influence "subjective" outcomes, including reports of discrimination among Mexican Americans. Our results reveal three main findings that illustrate the importance of local context. First, individuals living in a county with a greater share of co-ethnics report fewer experiences with discrimination. Second, in counties with an exclusionary ordinance, share of co-ethnics increases reports of discrimination. Finally, being born in the U.S. and speaking English do not provide protection from discrimination; rather, such characteristics shield Mexican Americans from discrimination only in contexts with larger shares of co-ethnics.